Applied Aspects of Modern Metrology - Velychko, Oleh (IntechOpen, 2022)
In the modern era of scientific and technological development, the role of measurements and metrology in scientific research is becoming more and more important due to the increase in the testing of various products. Moreover, requirements for the accuracy and reliability of measurement results are increasing significantly and their ranges are expanding. Improving measurement accuracy allows us to identify the shortcomings of certain technological processes and either eliminate them or reduce their influence. This leads to better-quality products and contributes to saving energy and other resources, as well as raw materials and materials. This book discusses relevant aspects of practical metrological activity to establish traceability of measurements while increasing their accuracy and reliability. It also presents procedures for the calibration and testing of measuring instruments.